Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please suggest an approach for this task.

share|improve this question
2  
Type "sum 1/(n(n+1)(n+2)(n+3))" into wolfram alpha. –  Oscar Cunningham Sep 27 '10 at 13:34
add comment

3 Answers

up vote 8 down vote accepted

$\dfrac{1}{k(k+1)(k+2)(k+3)} = \dfrac{1}{3} (\dfrac{k+3}{k(k+1)(k+2)(k+3)} - \dfrac{k}{k(k+1)(k+2)(k+3)})$ $ = \dfrac{1}{3}(\dfrac{1}{k(k+1)(k+2)} - \dfrac{1}{(k+1)(k+2)(k+3)})$

$\sum_{k=1}^{\infty}\dfrac{1}{k(k+1)(k+2)(k+3)} = \dfrac{1}{3} \dfrac{1}{2*3} = \dfrac{1}{18}$

@moron Yes, you are right. For the first n terms:

$\sum_{k=1}^{n}\dfrac{1}{k(k+1)(k+2)(k+3)} = \dfrac{1}{3} (\dfrac{1}{1*2*3} - \dfrac{1}{(n+1)(n+2)(n+3)})$

[edit] more details

$\sum_{k=1}^{n}\dfrac{1}{k(k+1)(k+2)(k+3)} = \sum_{k=1}^{n} \dfrac{1}{3} (\dfrac{1}{k(k+1)(k+2)} - \dfrac{1}{(k+1)(k+2)(k+3)})$ $= \dfrac{1}{3} [\sum_{k=1}^{n} \dfrac{1}{k(k+1)(k+2)} - \sum_{k=1}^{n} \dfrac{1}{(k+1)(k+2)(k+3)}]$ $= \dfrac{1}{3} [\sum_{k=0}^{n-1} \dfrac{1}{(k+1)(k+2)(k+3)} - \sum_{k=1}^{n} \dfrac{1}{(k+1)(k+2)(k+3)}]$ $= \dfrac{1}{3} (\dfrac{1}{1*2*3} - \dfrac{1}{(n+1)(n+2)(n+3)})$

share|improve this answer
2  
+1: Even though the question says first n terms, this can easily be adapted for that. –  Aryabhata Sep 27 '10 at 14:09
    
@Moron Thank for your comment –  Branimir Sep 27 '10 at 14:15
1  
@Branimir: You are welcome! And I see you joined today, welcome to this site :-) –  Aryabhata Sep 27 '10 at 14:20
    
so tricky!!! :) –  BBischof Sep 27 '10 at 14:21
    
Say n = 2, then 1/24 + 1/180 = 1/20 where as your solution is giving 1/18 - 1/72 = 1/24 ?! –  Quixotic Sep 27 '10 at 14:49
show 3 more comments

This is similar to what has been said by Branimir, but shows how we can extend the result to $$\sum_{k=1}^n {1 \over k(k+1) \cdots (k+m)}, \qquad m \in \mathbb{N}.$$

We can build up the result from the identities $${1 \over k(k+1)} = {1 \over k} - { 1 \over k+1}, \qquad (1)$$ $${1 \over k(k+1)(k+2)} = {1 \over 2} \left( {1 \over k(k+1)} - { 1 \over (k+1)(k+2)} \right),$$ $${1 \over k(k+1)(k+2)(k+3)} = {1 \over 3} \left( {1 \over k(k+1)(k+2)} - { 1 \over (k+1)(k+2)(k+3)} \right), \quad \textrm{ etc...}$$

Write $S_1 = \sum_{k=1}^n {1 \over k(k+1)},$ $S_2 = \sum_{k=1}^n {1 \over k(k+1)(k+2)},$ etc

Summing for $S_1$ using (1) all terms on RHS cancel to get the classic $$S_1 = \sum_{k=1}^n {1 \over k(k+1)} = 1 – {1 \over n+1} = {n \over n+1}.$$ We then sum the series for $S_2$ using this result obtained for $S_1,$ and so on.

share|improve this answer
2  
This can be expressed by saying that "negative falling powers behave nicely with respect to the difference operator". See p.53 in "Concrete Mathematics" by Graham, Knuth & Patashnik. –  Hans Lundmark Sep 27 '10 at 15:22
add comment

HINT $\rm\displaystyle\ \frac{1}{(k+1)(k+2)(k+3)(k+4)} = \frac{1}{6(k+1)} - \frac{1}{2(k+2)}+\frac{1}{2(k+3)}-\frac{1}{6(k+4)}$

$\rm\ f(k+1)-f(k)\: = $ above $\rm\displaystyle\ \Rightarrow\ f(k) \:=\: c_0 + \frac{c_1}{k+1}\ \:+\:\ \frac{c_2}{k+2}\ \:+\:\ \frac{c_3}{k+3}$

Calculating yields $\rm\ c_0,c_1,c_2,c_3 \ =\ 1/18,\ -1/6,\ 1/3,\ -1/6$.

For remarks on the group theory behind rational indefinite summation see my post here

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.